Vision difficulty and dementia: economic hardships among older adults and their caregivers - Kumar, Priyanka; Chung, Grace; Garcia-Morales, Emmanuel; Reed, Nicholas S.; Sheehan, Orla C.; Ehrlich, Joshua R.; Swenor, Bonnielin K.; Varadaraj, Varshini (Frontiers in Epidemiology, 2023)
Introduction: Limited research has examined the economic impact of vision difficulty (VD) and dementia on older adults and their caregivers. We aimed to determine whether older adults with VD and/or dementia, and their caregivers, face more economic hardships than their counterparts without VD or dementia.We used cross-sectional data from the 2015 National Health and Aging Trends Study (NHATS), a population-based survey of Medicare beneficiaries, linked to their family/unpaid caregivers from the National Study of Caregiving (NSOC). Regression models characterized the association of VD (self-report), dementia (survey and cognitive assessments), and co-occurring VD and dementia with debt, receiving financial help from relatives, government-based Supplemental Nutrition Assistance Program (SNAP), other food assistance, utility assistance, and caregiver financial difficulty.The NHATS sample included 6,879 community-dwelling older adults (5670 no VD/dementia, 494 VD-alone, 512 dementia-alone, 203 co-occurring VD and dementia). Adults with VD and dementia had higher odds of receiving SNAP benefits (OR=2.6, 95%CI=1.4-4.8) and other food assistance (OR=4.1, 95%CI=1.8-9.1) than adults without VD/dementia, while no differences were noted for debt, financial help, and utility assistance. Adults with VD-alone had higher odds of debt (OR=2.1, 95%CI=1.3-3.2), receiving financial help (OR=1.7, 95%CI=1.1-2.5) and other food assistance (OR=2.7, 95%CI=1.7-4.3); while adults with dementia-alone had higher odds of debt (OR=2.8, 95%CI=1.4-5.5). The NSOC sample included 1,759 caregivers (995 caring for adults without VD/dementia, 223 for VD-alone, 368 for dementia-alone, and 173 for co-occurring VD and dementia). Compared to caregivers of older adults without VD/dementia, caregivers of adults with VD and dementia had higher odds of financial difficulty (OR=3.0, 95%CI=1.7-5.3) while caregivers of adults with VD-alone or dementia-alone did not.Discussion: While older adults with VD-or dementia-alone experienced increased economic hardships, disparities in food assistance were amplified among older adults with co-occurring disease. Caregivers of adults with co-occurring disease experienced more financial difficulty than caregivers of adults with a single or no disease. This study highlights the need for interventions across clinical and social services to support the economic wellbeing of our aging population and their caregivers.